Open dumping site and health risks to proximate communities in Mumbai, India: A cross-sectional case-comparison study - Shri Kant Singh; Praveen Chokhandre; Pradeep S. Salve; Rahul Rajak (Elsevier, 2021)
Aim: Solid waste management is growing concern particularly in developing countries due its ill health effects to proximate communities. Study assess health effects of dumping site among nearby community members and identifying potential risk factors. Methods: A cross-sectional household survey was conducted using a case comparison design. Study population consisted of an exposed group and non-exposed group (nearby and a distant community respectively; n=200 each) having similar socio-economic and living conditions. To assess the health effects of dumping site, data on selected morbidities has been analyzed using the Propensity Score Matching (PSM) method. Results: The study findings suggest a relatively higher prevalence of selected morbidities among exposed group than non-exposed group particularly for respiratory illness (23% v 10%), eye irritation (20% v 9.5%) and for stomach problem (27% v 20%) respectively. Result from PSM suggest that exposure to the dumping site leads to a higher prevalence of respiratory illness (12%), eye irritation (8%) and stomach problems (7%). Multivariate analysis suggest respondents from the exposed group were significantly more likely to suffer from respiratory illness (OR 3.06, p < 0.01), eye infection (OR 2.39, p < 0.01) and stomach problems (OR 1.66, p < 0.05). Assessment of air-quality-index suggests poor levels of PM10 and PM2.5 during fire broke-out in Deonar dumping site. Conclusion: Study concludes that the prevalence of morbidities found to be significantly higher among the exposed group than non-exposed group particularly it is significantly higher for respiratory illness and eye infection. The propensity score matching methods reinstate that morbidities found to be significantly higher among exposed group than non-exposed group.